Genetic divergence of sweet potato genotypes based on morpho-agronomic traits - Oliveira, Darllan Jlsf De [UNESP]; Otoboni, Maria Eduarda F [UNESP]; Pavan, Bruno E [UNESP]; Andrade, Maria Isabel; Vargas, Pablo F [UNESP] (Associação Brasileira de Horticultura, 2021)
Sweet potato is a vegetable of great importance in human consumption, due to its high nutritional value. It presents high phenotypic variation, with different forms of roots, leaves and vines. Given the above, we aimed to study the genetic divergence of sweet potato genotypes based on morpho-agronomic traits. The experiment was conducted in an experimental area of Unesp, Ilha Solteira Campus, located in Selvíria-MS. The experimental design used was randomized blocks with two replicates, including 200 genotypes and ‘Beauregard’ as a biofortified control. Shoot morphological traits of the genotypes were evaluated at 110 days and root morphological traits were evaluated at 127 days after planting. We used the obtained data to perform descriptive analysis, in percentage of phenotypic classes. In order to study genetic divergence, multivariate analysis was performed, grouping was done using Tocher’s and Ward’s methods. We also analyzed relative contribution of each trait for genetic divergence. Statistical analyzes were performed using Genes software and SAS. Wide genetic variability could be verified in the population studied in this experiment, being possible to obtain genetic gains in recombination between genotypes. Grouping using Tocher’s method was more effective for discriminating dissimilarity between genotypes. The low relative importance of leaf size, internode diameter and secondary peel color makes further evaluation of these traits unnecessary, reducing labor costs, cost and execution time.

A batata-doce é uma hortaliça de grande importância na alimentação humana, devido ao seu alto valor nutritivo. Apresenta alta variação fenotípica, com diversas formas de raízes, folhas e ramas. Diante do exposto, objetivou-se estudar a divergência genética de genótipos de batata-doce por meio de caracteres morfoagronômicos. O experimento foi conduzido em área experimental da Unesp, Câmpus de Ilha Solteira, situada no município de Selvíria-MS. O delineamento experimental utilizado foi de blocos casualizados com duas repetições, incluindo 200 genótipos e ‘Beauregard’ como testemunha biofortificada. Foram avaliados caracteres morfoagronômicos de parte aérea dos genótipos aos 110 dias e de raiz aos 127 dias, após o plantio. Com os dados obtidos realizou-se análise descritiva em percentual das classes fenotípicas. Para estudo da divergência genética realizou-se análise multivariada, agrupando-se pelos métodos de Tocher & Ward. Também realizou-se análise da contribuição relativa de cada carácter para a divergência genética. As análises estatísticas foram feitas utilizando-se o programa computacional Genes e SAS. Há ampla diversidade genética na população estudada, o que pode possibilitar ganhos genéticos na recombinação dos genótipos. O método de agrupamento de Tocher foi mais efetivo para discriminação da dissimilaridade entre os genótipos. A baixa importância relativa dos caracteres tamanho da folha, diâmetro do internódio e cor secundária da casca, permite dispensar a sua análise em futuros trabalhos, reduzindo gastos de mão-de-obra, custo e tempo de execução.
Divergência genética de genótipos de batata-doce por meio de caracteres morfoagronômicos
Keywords: Ipomoea batatas; germplasm bank; breeding; biofortification; Ipomoea batatas; banco de germoplasma; melhoramento genético.; biofortificação